2002
DOI: 10.1103/physrevb.65.205115
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of photoelectrons participating in formation of x-ray absorption spectra

Abstract: Interpretation of x-ray absorption near-edge structure (XANES) experiments is often done via analyzing the role of particular atoms in the formation of specific peaks in the calculated spectrum. Typically, this is achieved by calculating the spectrum for a series of trial structures where various atoms are moved and/or removed. A more quantitative approach is presented here, based on comparing the probabilities that a XANES photoelectron of a given energy can be found near particular atoms. Such a photoelectro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The relative roles of individual atomic sites in the formation of a particular spectral peak can be quantitatively assessed by comparing the wave function probability densities (WFPD) around those sites [8]. By performing this analysis for all the three edges, we found that the excited photoelectron is located almost exclusively on Fe atoms at the pre-peak energy; the calculated WFPD around the Fe sites is by three orders of magnitude higher than around any of the Cu or S sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative roles of individual atomic sites in the formation of a particular spectral peak can be quantitatively assessed by comparing the wave function probability densities (WFPD) around those sites [8]. By performing this analysis for all the three edges, we found that the excited photoelectron is located almost exclusively on Fe atoms at the pre-peak energy; the calculated WFPD around the Fe sites is by three orders of magnitude higher than around any of the Cu or S sites.…”
Section: Resultsmentioning
confidence: 99%
“…In order to facilitate the interpretation of the pre-edge region in CuFeS 2 , wave function probability densities associated with the excited photoelectron were calculated in the RSMS formalism [8]. In that way, one can gain a well-defined picture of the spatial distribution of the photoelectrons which participate in the formation of specific XANES features.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%